JIWA MANUSIA DALAM PANDANGAN PLATO - Simorangkir, Hieronymus (LOGOS, 2004)
Self-knowledge, as Socrates and later Plato demonstrated, is acquired by a reflective and rational analysis of the universal nature of man. According to Plato, to know oneself (in this objective sense) means to have a rational knowledge of the relation of man to the whole of nature. Plato’s Republic is based upon the thesis that the prerequisite for a scientific knowledge of man is a knowledge of mathematics and of the unchanging mathematical forms manifested in nature as a whole. The idea of the Good is the principle of integration in the cosmos as a whole and can therefore be known and intuited only through a prior knowledge of physics and astronomy.1 Only meta-physical, theoretical or dialectical knowledge of this kind can provide a solid foundation upon which to build the organization of man’s social and cultural life. In short, genuine self-knowledge involved an ontological and theoretical analysis of nature as a whole.